AGGRESSIVENESS OF THE MANURING WITH SILICON ABOUT THE GERMINATION OF THE CORN - CARVALHO FILHO, Alberto; PEREIRA, Leandro Jorge; CORTEZ, Jorge Wilson; CARVALHO, Luis Carlos Cirilo; DRUMOND, Luis César Dias (Scientia Agraria, 2007)
With the objective of evaluating the decrease of the aggressiveness of the fertilizers to the root system of the corn, it was added to the fertilizers powdered Agro-silicon. The treatments were: T1 = 0 kg ha-1 of Agro-silicon (check plot); T2 = 100 kg ha-1 of Agro-silicon; T3 = 200 kg ha-1 of Agro-silicon; T4 = 300 kg ha-1 of Agro-silicon. It was evaluated: length root system of the corn to each stage, during the first 30 days after the emergency of the plantule (DAE) and pH of the soil in the sowing furrow to the 15 and 30 DAE. It was observed that the root length in the stage VE (before the first "true" pair's of leaves appearance) it increases until the treatment with 200 kg ha-1 to leave of that there is decrease of the growth. In the stages V1 (first pair of leaves) and V2 (second equal of leaves) there was not effect of the treatments. In the stage V3 (third equal of leaves developed), it happened lineal increase for the applied doses. The pH of the soil was not influenced by any of the treatments.